Flexible multivariate geospatial data visualization system / Fatin Farhana Badrul Hisham - Badrul Hisham, Fatin Farhana (Faculty of Computer and Mathematical Sciences, 2017)
Geospatial data visualization is a point marked in a map where the points were determined by longitude and latitude. Visualization are needed because it can give pattern of the attributes in much variety other than viewing the raw data that can cause overlook. To use the visualization technique, user must have a knowledge about two or more programming language as well learn on how to work or maybe build one from scratch. To overcome this problem, a platform to visualize multivariate geospatial data were made to ease the user. This system required user to upload the data set and it will automatically visualize it in either symbol map or dot map and allowed user to interact with the data as well as reduce user’s time to build or to learn to code the visualization. Symbol map is a map that visualize attribute values for the location and the size of the marker is corresponding to the value meanwhile Dot map are based on spatial point data where information consist location are given. 57% of the user shows that they are strongly agree about the system was easy to use with the other 43% of the user are agreeing together. The limitation of this system is that user must convert into either JSON or CSV file format first before uploading the file for visualization process. Finally, this flexible multivariate geospatial data visualization system is significant in areas of user in any background who want to visualize a multivariate data.